ABOUT THE DYNAMICS AND ROTATION OF THE ARTIFICIAL SATELLITES - Epichev, V. P.; Bratijchuk, M. V.; Isak, I. I. (Одеські астрономічні публікації, 2017)
In the present work the results of the investigation of the unguided artificial objects which belong nowadays to Space Debris, have been considered. The experience of the analysis of these results has proved that such objects may serve indicators in basic perturbating moment study. One of the methods of perturbation reveling is investigation of the objects orientation changes in space.